Passively Q-switched and mode-locked Erbium-doped fiber laser with topological insulator Bismuth Selenide (Bi2Se3) as saturable absorber at C-band region - Haris, Hazlihan; Arof, Hamzah; Muhammad, Ahmad Razif; Anyi, Carol Livan; Tan, Sin Jin; Kasim, Nabilah; Harun, Sulaiman Wadi (Elsevier, 2019)
We experimentally demonstrate Q-switched and mode-locked Erbium-doped fiber laser (EDFL) by using topological insulator (TI) Bismuth Selenide (Bi2Se3) as saturable absorber (SA). The fabricated Bi2Se3 SA exhibits modulation depth and saturation intensity at 39.8% and 90.2 MW/cm2, respectively. By incorporating the fabricated Bi2Se3 SA into the laser cavity, Q-switching operation is generated with repetition rate ranging from 23.5 kHz to 68.2 kHz, pulse width ranging from 2.4 μs to 8.6 μs and maximum peak power is calculated at 19.9 mW. Our cavity can also generate soliton mode-locked pulse with repetition rate of 23.3 MHz and pulse width of 0.63 ps by inserting an additional 5 m long single mode fiber (SMF) into the existing laser cavity. Spectral peaks due to Kelly side-bands and four wave mixing (FWM) were observed on the soliton spectrum. Both Q-switching and mode-locking pulses are stable in the laboratory environment, allowing the realization of compact and low cost pulsed fiber laser with Bi2Se3 SA for various photonics applications.